Hand prosthesis control using muscular contractions from residual upper-limb of amputee - Prakash, Alok (IIT(BHU) Varanasi, 2020)
Abstract is available in content.
Keywords: Hand prosthesis control using; muscular contractions from; residual upper-limb of amputee